The attitudes of united states and South African managers to corporate social responsibility - Orpen, Christopher (Journal of business ethics, 1987)
The attitudes of 164 United States and 151 South African managers towards corporate social responsibility were assessed. The United States managers held significantly more favourable attitudes towards corporate social responsibility. In addition, they agreed with more pro-responsibility arguments, whereas the South African managers agreed with more anti-responsibility arguments. The United States managers felt that their society expected more corporate involvement in social responsibility activities than the South African managers felt was expected from their society. The results are explained in terms of the susceptibility of social responsibility attitudes to cultural norms and values — which reflect the different nature of the two societies.